2017
DOI: 10.1007/s13204-017-0595-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and catalytic activity of nanosized Ni complexed aminoclay

Abstract: A novel Ni complexed aminoclay (AC) catalyst was prepared by complexation method followed by reduction reaction. Various analytical techniques such as FTIR spectroscopy, UV-visible spectroscopy, DSC, TGA, SEM, HRTEM, EDX, XPS and WCA measurement are used to characterize the synthesized material. The AC-Ni catalyst system exhibited improved thermal stability and fiber-like morphology. The XPS results declared the formation of Ni nanoparticles. Thus, synthesized catalyst was tested towards the Schiff base format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…These results confirmed that the Ni ions of polyNi have an octahedral coordination structure. Additionally, the double peaks appeared around 865 eV (Ni 2P 3/2 ) and 883 eV (Ni 2P 1/2 ) in the X-ray photoelectron spectrum of polyNi (Figure S9) also confirm the presence of Ni­(II) ions …”
Section: Resultsmentioning
confidence: 60%
“…These results confirmed that the Ni ions of polyNi have an octahedral coordination structure. Additionally, the double peaks appeared around 865 eV (Ni 2P 3/2 ) and 883 eV (Ni 2P 1/2 ) in the X-ray photoelectron spectrum of polyNi (Figure S9) also confirm the presence of Ni­(II) ions …”
Section: Resultsmentioning
confidence: 60%
“…The k app for 25, 50, 75, and 100 mM are 0.433, 0.076, 0.027, and 0.0019 s −1 , respectively. This is due to the inability of CuNWs to relay excess electrons [55,56].…”
Section: Resultsmentioning
confidence: 99%
“…25 However, as mentioned, the rate constant for the 8 g L -1 concentration of NaBH 4 is observed to decrease. This is caused by excessive production of electrons from the ion leading to the saturation of electrons 70 leaving AgNPs incapable of relaying the electrons.…”
Section: Effect Of Amount Of Nabhmentioning
confidence: 99%